Prevalence of diabetes and impaired fasting glucose in Poland in 2005–2014: results of the WOBASZ surveys. Issue 9 (1st June 2020) - Rutkowski, M.; Wojciechowska, A.; Śmigielski, W.; Drygas, W.; Piwońska, A.; Pająk, A.; Tykarski, A.; Kozakiewicz, K.; Waśniewska, M. K; Zdrojewski, T.
Abstract: Aims: To evaluate the prevalence of diabetes and impaired fasting glucose in Poland in 2013–2014 and to determine the temporal trends between 2003–2005 and 2013–2014. Methods: A questionnaire survey was conducted in a representative sample of Polish adults, complemented by anthropometric and fasting plasma glucose measurements. The research was part of the national cross‐sectional WOBASZ study. Diabetes was assessed as self‐reported or screened (fasting plasma glucose level ≥ 7 mmol/l, based on one blood sample). Results: In the years 2013–2014 among 5694 participants aged 20–74 years, 6.0% (95% CI 5.4–6.6) reported a previous diagnosis of diabetes (5.8% in women and 6.2% in men). In addition, 2.4% of the participants (95% CI 2.0–2.8) without a previous diagnosis of diabetes (1.8% of women and 3.1% of men) had a fasting blood glucose level ≥7.0 mmol/l in a single measurement. In a single measurement, 18.4% of the participants (95% CI 17.4–19.4; 13.2% of women and 23.8% of men) had impaired fasting glucose. The prevalence of dysglycaemia in the WOBASZ II study was significantly higher compared to the WOBASZ I study findings from 2003–2005, increased from 6.6% to 8.4% for diabetes and from 9.3% to 18.4% for impaired fasting glucose (after age and sex standardization to the 2013 Polish population). Conclusions: The prevalence of diabetes in Poland is similar to that observed in other European populations and has increased significantly over the last decade. What's new?: The prevalence of diabetes (for type 1 and type 2) in Poland in 2014 is 8.4% and is similar to that in other European countries. More than every fourth person with diabetes is unaware of their disease. The prevalence of diabetes has increased significantly over the last decade (2004–2014), from 6.6% to 8.4%.